Quantitative proteomics revealed new functions of ALKBH4. Issue 7 (5th January 2022) - Yu, Kailin; Qi, Tianyu F.; Miao, Weili; Liu, Xiaochuan; Wang, Yinsheng
Abstract: ALKBH4 is a versatile demethylase capable of catalyzing the demethylation of monomethylated lysine‐84 on actin and N 6 ‐methyladenine in DNA. In this study, we conducted a quantitative proteomic experiment to reveal the altered expression of proteins in HEK293T cells upon genetic ablation of ALKBH4 . Our results showed markedly diminished levels of GSTP1 and HSPB1 proteins in ALKBH4‐depleted cells, which emanate from an augmented expression level of DNA (cytosine‐5)‐methyltransferase 1 (DNMT1) and the ensuing elevated cytosine methylation in the promoter regions of GSTP1 and HSPB1 genes. Together, our results revealed a role of ALKBH4 in modulating DNA cytosine methylation through regulating the expression level of DNMT1 protein.